Immunogenicity of a Bovine Herpes Virus I Peptide Expressed in Tandem Copies in Attenuated Salmonella - Gnazzo, Victoria (2012)
A live system to release heterologous antigens using an attenuated Salmonella strain was developed. We transformed Salmonella typhimurium LVR03 (S. LVR03) with a recombinant pTECH2 vector encoding 0, 1, 2, and 4 tandem copies of an imunogenic peptide of bovine herpes virus-1 (BoHV-1) glycoprotein D (gD). The system used yielded peptides fused to the non-toxic C fragment of the tetanus toxin (TetC), which has been shown to have adjuvant properties. Inoculation of BALB/c mice with the transformed Salmonella strains gave rise to a mild self-limited infection, with primary replication of bacteria occurring in Peyer´s patches, even when the bacteria was administered intranasally. Humoral and cellular immune responses directed against the BoHV-1 antigens were evaluated after oral or intranasal administration of the recombinant bacteria. The results showed that the S. LVR03-dimer vaccine induced specific humoral (IgG in serum and IgG(1) and IgA in saliva), and cellular immune responses (lymphoproliferation and lymphokine secretion), against not only the selected peptide and whole gD, but also against BoHV-1, when administered intranasally. This is the first time Salmonella has been used as an expression vector to induce immunity against BoHV-1. This work demonstrates the feasibility of using this antigen-release system and encourages future experimentation with a bovine experimental model.